Implementation of blood glucose self-monitoring among insulin-dependent patients with type 2 diabetes in three rural districts in Rwanda: 6 months open randomised controlled trial. Issue 7 (27th July 2020) - Ng'ang'a, Loise; Ngoga, Gedeon; Dusabeyezu, Symaque; Hedt-Gauthier, Bethany L; Ngamije, Patient; Habiyaremye, Michel; Harerimana, Emmanuel; Ndayisaba, Gilles; Rusangwa, Christian; Niyonsenga, Simon Pierre; Bavuma, Charlotte M; Bukhman, Gene; et al.
Abstract : Introduction: Most patients diagnosed with diabetes in sub-Saharan Africa (SSA) present with poorly controlled blood glucose, which is associated with increased risks of complications and greater financial burden on both the patients and health systems. Insulin-dependent patients with diabetes in SSA lack appropriate home-based monitoring technology to inform themselves and clinicians of the daily fluctuations in blood glucose. Without sufficient home-based data, insulin adjustments are not data driven and adopting individual behavioural change for glucose control in SSA does not have a systematic path towards improvement. Methods and analysis: This study explores the feasibility and impact of implementing self-monitoring of blood glucose (SMBG) in patients with type 2 diabetes in rural Rwandan districts. This is an open randomised controlled trial comprising of two arms: (1) Intervention group—participants will receive a glucose metre, blood test strips, logbook, waste management box and training on how to conduct SMBG in additional to usual care and (2) Control group—participants will receive usual care, comprising of clinical consultations and routine monthly follow-up. We will conduct qualitative interviews at enrolment and at the end of the study to assess knowledge of diabetes. At the end of the study period, we will interview clinicians and participants to assess the perceived usefulness, facilitators and barriers of SMBG. The primary outcomes are change in haemoglobin A1c, fidelity to SMBG protocol by patients, appropriateness and adverse effects resulting from SMBG. Secondary outcomes include reliability and acceptability of SMBG and change in the quality of life of the participants. Ethics and dissemination: This study has been approved by the Rwanda National Ethics Committee (Kigali, Rwanda No.102/RNEC/2018). We will disseminate the findings of this study through presentations within our study settings, scientific conferences and publication in a peer-reviewed journal. Trial registration number: PACTR201905538846394; pre-results.